If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 = -3 + z Solving 11 = -3 + z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. 11 + -1z = -3 + z + -1z Combine like terms: z + -1z = 0 11 + -1z = -3 + 0 11 + -1z = -3 Add '-11' to each side of the equation. 11 + -11 + -1z = -3 + -11 Combine like terms: 11 + -11 = 0 0 + -1z = -3 + -11 -1z = -3 + -11 Combine like terms: -3 + -11 = -14 -1z = -14 Divide each side by '-1'. z = 14 Simplifying z = 14
| 24x+4=19x+4 | | 3x-(4x+6)=x-9 | | 11=-4.9t^2+120t | | 10x^2+12x-1=4x | | 8-(5/7)x-32 | | 2w+3(w+2)+2(w+5)=44 | | -10+k=10-9k | | -9j+10=10j | | -4a+16+6a=-9a | | (7x+3)(x-5)=-2x(5x+6)+x-19 | | -6-7f=-6f | | X-27=84 | | t-10=10-9t | | 2+7cosx=4sin^2x | | 12x+14=134 | | y+2(y+3)+3(y+1)=45 | | 4p-7.3=16.7 | | 8-2w=-w | | -6n=-6-7n | | 8r+10=9r | | 1/5n=-8 | | 2r+3(r+3)+3r=1 | | x^2+18x+73=-9 | | y=-4.9t^2+120t | | 270=920(1-d) | | 8.7=3.5m-3.5(5.4-6m) | | 4a+5(a+3)+-14=64 | | -10-3p=10-5p-8 | | 4m^2n-6n^2-2mn= | | 3(5z+1)-12=13z+3 | | -2-6=-8u | | -4=3x+6 |